2016
DOI: 10.1007/s10973-016-5636-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and thermodynamic re-assessment of the Mn–Nd binary system

Abstract: Fourteen Mn-Nd alloys were investigated experimentally by means of thermal analysis. The temperatures of the invariant reactions and liquidus in the Mn-Nd binary system were determined. Based on the experimental results obtained in the present work as well as the experimental data reported and the previous assessments in the literature, the Mn-Nd binary system was re-assessed thermodynamically using the CALPHAD method. The solution phases, including liquid, a-Mn, b-Mn, c-Mn, d-Mn, a-Nd and d-Nd, are modeled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Phase equilibria of the Mn‐Ho binary system were studied experimentally, [41,47] and were calculated by Wang et al., [49] Kim et al., [20] and Wang et al [24] . According to the reported experimental data and calculations, five Mn‐RE (RE = La, Nd, Gd, Dy, and Ho) binary systems were reassessed in our group [21–24] . The calculated results are consistent well with the experimental data.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Phase equilibria of the Mn‐Ho binary system were studied experimentally, [41,47] and were calculated by Wang et al., [49] Kim et al., [20] and Wang et al [24] . According to the reported experimental data and calculations, five Mn‐RE (RE = La, Nd, Gd, Dy, and Ho) binary systems were reassessed in our group [21–24] . The calculated results are consistent well with the experimental data.…”
Section: Introductionsupporting
confidence: 80%
“…There are three stable intermetallic compounds, Mn 12 Tb, Mn 23 Tb 6 , and Mn 2 Tb in the Mn‐Tb binary system. It was observed that the reported experimental results [34] are not consistent with the new experimental data in the Mn‐RE (RE = Nd, Gd, Dy, and Ho) binary systems [22–24] . Therefore, it is reasonable the calculated Mn‐Tb binary phase diagram shows a slight deviation from the experimental data [34] .…”
Section: Calculated Resultsmentioning
confidence: 73%
See 3 more Smart Citations